Analysis of the effect of the regional minimum wage rate (umr) and inflation on investment levels in North Sumatra in 2002-2016 - Taqwa, Zadit (Institute of Accounting Research and Novation (IARN), 2023)
This study aims to find out how the influence of the Regional Minimum Wage (UMR) and Inflation on Investment in North Sumatra in 2002-2016. This research is a quantitative research. The data used comes from BKPM (Investment Coordinating Board) and BPS (Central Statistics Agency). The data analysis used in this study is multiple linear regression analysis using the Ordinary Least Square (OLS) method using the EVIEWS version 8 program. The results show that: 1) Regional Minimum Wage (UMR) significantly positively affects investment in North Sumatra with a probability value of 0 .0000 is less than the significance level (5%) or 0.0000 < 0.05. 2) Inflation does not have a significant negative effect on investment in North Sumatra with a probability value greater than the significance level (5%) or 0.9128 > 0.05. 3) The results of the study simultaneously show that the Regional Minimum Wage (UMR) and inflation have a significant effect on investment in North Sumatra with a probability value (F-statistic) smaller than the significance level (5%) or 0.000007 <0.05. The determination test shows that around 0.861279 or 86.1% of the Regional Minimum Wage (UMR) and inflation variables can explain investment in North Sumatra in the 2002-2016 period, while the remaining 13.9% is explained by other factors.